SEJARAH DAN PERKEMBANGAN PERSIS - Shifna Hafidhotul Mar’ah; Najwa Zakiyya Husna; Firnanda Titania Dzulfa (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2024)
This research aims to explore the history of the establishment of Persatuan Islam (PERSIS) and its contributions to Indonesian society. The study uses a narrative method with literature review to present the journey of this organization since its founding in 1923. PERSIS was founded by K.H. Zamzam and other figures such as Ahmad Hassan and Mohammad Natsir, who played significant roles in education and politics. As an organization focused on Islamic reform, PERSIS strives to return Islamic teachings to their original sources, the Qur'an and Hadith, and contributes to education and social welfare. The initial curriculum of PERSIS emphasized the integration of religious and general education, aiming to form cadres capable of spreading Islamic teachings. The organization successfully established many pesantren and educational institutions across Indonesia and played a role in the Islamic reform movement. PERSIS is also active in preaching and social activities, as well as engaging in contemporary Islamic discussions. This research concludes that PERSIS remains relevant and influential in the social and religious dynamics in Indonesia.